Accuracy and Physical Characterization of Approximate Arithmetic Circuits - Catelan, Daniela; Santos, Ricardo; Duenha, Liana (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2020: Anais do XXI Simpósio em Sistemas Computacionais de Alto Desempenho, 2020)
With the end of Dennard's scale, designers have been looking for new alternatives and approximate computing (AC) has managed to attract the attention of researchers, by offering techniques ranging from the application level to the circuit level. When applying approximate circuit techniques in hardware design, the program user may speed up the application while a designer may save area and power dissipation at the cost of less accuracy on the operations results. This paper discusses the compromise between accuracy versus physical efﬁciency by presenting a set of experiments and results of tailor-made approximate arithmetic circuits on Field-Programmable Gate Array (FPGA) platforms. Our results reveal that an approximate circuit with accuracy control could not be useful if the goal is to save circuit area or even power dissipation. Even for circuits that seem to have power efﬁciency, we should care about the size and prototyping platform where the hardware will be used.